Proceso de descarga emocional y su incidencia en el desempeño laboral del área operativa del Sistema Integrado de Seguridad ECU-911 Babahoyo, periodo 2023. - Maliza Muñoz, Patricio Marcelo (2024)
This study was developed at the ECU-911 Babahoyo Integrated Security System, located in the city of Babahoyo. This research focuses on the emotional discharge process, understood as the expression and management of emotions in the work context. The nature of the situations that ECU-911 Babahoyo workers face, which may involve emergencies and crises, generates a high level of emotional stress, making it crucial to understand how this emotional discharge influences their job performance. The main objective of the research was to analyze the impact of the emotional discharge process on the job performance of the personnel in the operational area of the ECU-911 Babahoyo Integrated Security System during the period 2023. The research methodology was descriptive because it explains the variables under study. The results determined that it was concluded that stress is a problem present among the operational staff of ECU-911 Babahoyo, serious emergency situations are the main contributing factor to work stress, the relationship between emotional discharge and job performance in the operational staff of ECU-911 Babahoyo is evident and significant.